Ultrasound assisted biodiesel production in presence of dolomite catalyst - Korkut, Ibrahim; Bayramoglu, Mahmut (Elsevier Sci Ltd, 2016)
Ultrasound (US) assisted transesterification of canola oil in presence of heterogeneous catalysts calcined dolomite and CaO was investigated in comparison to each other. An US generator (200 W, 20 kHz) equipped with an horn type probe (19 mm) was used to study the effect of catalyst amount (3-7 wt.% of oil), methanol/oil molar ratio (4/1-15/1), ultrasound power (30-50 W), temperature (25-60 degrees C) and time (60-120 min) on US assisted biodiesel synthesis. Biodiesel yield reached over 97.4% for calcined dolomite at the end of 90 min and 95.5% for CaO at the end of 75 min. According to the results, US improved the transesterification reaction by reducing necessary time for high biodiesel yield, using calcined dolomite as well CaO as heterogeneous catalyst. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Ultrasound; Dolomite; CaO; Biodiesel synthesis; Heterogeneous catalyst